Analisis Pendekatan Individual dalam Pembelajaran Pendidikan Agama Islam pada Siswa ADHD di Sekolah Alam Tangerang Mekar Bakti - Stiyani, Lenia Dwi Stiyani; Yayah Nurmaliyah; Abdul Ghofur (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2025)
The learning approach is one of the most important supports for the success of the learning process in inclusive schools. Using an appropriate learning approach will make it easier for students to understand the material taught. This applies to learning for children with ADHD. However, in reality, in the learning process for children with ADHD, there are still inclusive schools that do not use effective learning approaches, especially for children with ADHD. Therefore, this research aims to find out how to use the Individual Approach in the Islamic Education learning process for ADHD students at the Tangerang Nature School Mekar Bakti. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation studies. The results of this study explain that the use of the Individual Approach in Islamic Education learning for ADHD students at the Tangerang Mekar Bakti Nature School includes planning, implementation and evaluation activities. Planning activities are prepared through initial observations carried out by the school and psychologists, this is done to analyze the initial condition of the students. Implementation of the Individual Approach in Islamic Education learning for ADHD students at the Tangerang Nature School Mekar Bakti is carried out using the Cluster and Pull Out model. In the process, the learning media uses flash cards, cellphones, puzzles and playdough. Evaluation of the use of the Individual Approach in Islamic Education learning for ADHD students is carried out routinely by inclusion teachers and PAI teachers who discuss the development of each ADHD child who is guided by the Shadow Teacher. It is hoped that this research can be a motivation for educational institutions for children with special needs, especially children with ADHD, in implementing an Individual Approach in Islamic Education learning.